2013
DOI: 10.1136/bjsports-2012-092101.23
|View full text |Cite
|
Sign up to set email alerts
|

Do family physicans, emergency physicians and paediatricians give consistent sport-related concussion management advice?

Abstract: ObjectiveTo identify differences and gaps in the recommendations to patients for the management of sport-related concussion among family physicians (FPs), emergency physicians (ERs) and paediatricians (Peds).DesignA self-administered multiple-choice survey, which had been validated for content validity.SettingToronto East General Hospital and Markham Stouffville Hospital, both in Ontario, Canada.Subjects270 physicians were invited to participate; 104 surveys were completed (39%).InterventionThe survey link was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 0 publications
5
32
2
2
Order By: Relevance
“…21,38 No attention was given to the needs of the PCP for knowledge transfer. This study implies that there may be a similar knowledge transfer problem with chiropractic PCPs and parallels other studies performed on medical practitioners, 19,30 indicating the need for further study. This study is unique in that it is the first study performed on primary-contact chiropractic physicians.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…21,38 No attention was given to the needs of the PCP for knowledge transfer. This study implies that there may be a similar knowledge transfer problem with chiropractic PCPs and parallels other studies performed on medical practitioners, 19,30 indicating the need for further study. This study is unique in that it is the first study performed on primary-contact chiropractic physicians.…”
Section: Discussionmentioning
confidence: 48%
“…26 Other studies have reported the deficient TBI knowledge of coaches, 27,28 medical students, 29 emergency physicians, and family medical physicians. 30 Knowledge of chiropractors has not been well researched, and there is a lack of any cohort medical doctor (MD)/doctor of chiropractic (DC) studies. Specific predoctoral training in diagnosis and management of TBI is not outlined by the Council on Chiropractic Accreditation Standards 31 and may vary between different training programs.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past several years there have been numerous studies evaluating the knowledge and awareness of concussion among athletes, 4,[28][29][30][31][32][33][34] parents, 34,35 and coaches. 36,37 Studies have also addressed health care providers' knowledge and use of various concussion management practices, 14,[38][39][40][41][42][43][44][45] yet findings from our study highlight that knowledge-to-practice gaps may still exist.…”
Section: Concussion Education and Awarenessmentioning
confidence: 73%
“…Stoller et al 16 reported that half of family practice and emergency department physicians had no knowledge of any consensus statement related to concussion in sport, whereas others discuss underreporting of concussion injuries. 1,2,4 This underscores the importance of having adequately trained staff present or readily available to athletes during times of practice and competition, especially for female athletes.…”
Section: Discussionmentioning
confidence: 99%